Woman’s Potrayal In Perempuan Yang Menangis Kepada Bulan Hitam Feminist Perspective - Dewi, Maharani; Muhammad Ilham Yasin; Moh Hilman Fikri (JURNAL PENDIDIKAN & PENGAJARAN (JUPE2), 2026)
ABSTRAK Penelitian ini bertujuan untuk menguak bagaimana perempuan digambarkan sebagai mahluk yang inferior tanpa kuasa jika tidak ada perlindungan lelaki. Perempuan Yang Menangis Kepada Bulan Hitam ini menceritakan diskriminasi tokoh perempuan dari adat Kawin Tangkap yang merujuk pada penculikan dan pemerkosaan. Dimana hal tersebut sangat merendahkan martabat perempuan dan sangat mendiskriminasi keberadaan perempuan sebagai mahluk yang bebas kehendak dan kuasanya. Perempuan dalam novel ini berusaha ditundukkan dengan superioritas laki-laki meski akhirnya perempuan sang tokoh utama dalam karya ini menunjukkan hasil bagaimana merebut kebebasan yang sudah dirampas paksa oleh lelaki. Metode kualitatif digunakan sebagai metode analisa dalam proses pengumpulan dan analisa data. Selain itu dihasilkan beberapa temuan tentang bagaimana perempuan digambarkan dalam novel antara lain, perempuan digambarkan sebagai manusia yang berfisik lemah; Kedua, perempuan digambarkan sebagai mahluk yang tak punya kuasa; Ketiga, perempuan digambarkan sebagai manusia yang harus menerima semua keputusan tanpa bantahan; Ke empat, perempuan digambarkan menjadi penurut yang harus menerima keputusan hanya karena dia perempuan; Kelima, perempuan digambarkan harus berjuang meski perjuangannya juga belum tentu banyak mendapatkan dukungan. Dapat disimpulkan bahwasanya, perempuan dalam masyarakat digambarkan sebagai manusia yang keberadaaannya terkungkung dalam bayang-bayang laki-laki, meski demikian perempuan seharusnya tetap memperjuangkan hak-haknya sebagai manusia bebas meski jalan yang ditempuh tak akan mudah. ABSTRACT This study aims to reveal the portrayal of women in social reality which has so far been exalting the power of men. How women are depicted as inferior and powerless creatures if there is no protection from men will be shown in the novel entitled Women Who Cry to the Black Moon. So that the focus of the problem that will be raised in this study is about how the depiction of women in Dian Purnomo's novel Perempuan Yang Menangis Kepada Bulan Hitam is portrayed. This novel tells the story of a woman's struggle against the discrimination she has received as a woman. Discrimination received by female marshal figures from the Kawin Tangkap custom which refers to kidnapping and rape. Where this is very demeaning to women's dignity and greatly discriminates against the existence of women as creatures who are free of will and power. Women in this novel are trying to be subdued by the superiority of the existence of men, even though in the end the woman as the main character in this work shows the result of how to seize the freedom that has been forcibly taken away by men. Qualitative method is used as an analytical method in the process of data collection and analysis. In addition, several findings were made about how women are depicted in the novel, among others, women are depicted as humans who are physically weak; Second, women are depicted as creatures who have no power; Third, women are depicted as human beings who must accept all decisions without objection; Fourth, women are depicted as submissive who have to accept decisions just because they are women; Fifth, women are described as having to struggle even though their struggles do not necessarily get a lot of support. So it can be concluded from the five depictions of women in the novel Perempuan Menangis Kepada Bulan Hitam that women in society are still depicted as human beings whose existence is confined in the shadows of men, but even so, women should still fight for their rights as free human beings even though it will not be an easy proccess to do.